1995
DOI: 10.1172/jci117761
|View full text |Cite
|
Sign up to set email alerts
|

Induction of sustained expression of proto-oncogene c-fms by platelet-derived growth factor, epidermal growth factor, and basic fibroblast growth factor, and its suppression by interferon-gamma and macrophage colony-stimulating factor in human aortic medial smooth muscle cells.

Abstract: Vascular medial smooth muscle cells migrate, proliferate and transform to foam cells in the process of atherosclerosis. We have reported that the intimal smooth muscle cells express proto-oncogene c-fms, a characteristic gene of monocyte-macrophages, which is not normally expressed in medial smooth muscle cells. In the present study, we demonstrated that combinations of platelet-derived growth factor (PDGF)-BB and either epidermal growth factor (EGF) or fibroblast growth factor (FGF) induced high expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…10,11 Furthermore, it has been reported that overexpression of PDGF, c-myc and other protooncogenes occurs in atherosclerotic vascular lesions. [11][12][13] The monoclonal hypothesis is also consistent with the observations that carcinogenic agents, like chemical mutagens, radiations and oncogenic viruses, can induce atherosclerotic lesions in laboratory animals and have atherogenic effects in human population. 2,[14][15][16][17][18][19] Certainly, the "response to injury" and the "monoclonal" theories of atherosclerosis are not mutually exclusive and can be unified as described in Figure 2.…”
Section: The Development Of Atherosclerosissupporting
confidence: 69%
“…10,11 Furthermore, it has been reported that overexpression of PDGF, c-myc and other protooncogenes occurs in atherosclerotic vascular lesions. [11][12][13] The monoclonal hypothesis is also consistent with the observations that carcinogenic agents, like chemical mutagens, radiations and oncogenic viruses, can induce atherosclerotic lesions in laboratory animals and have atherogenic effects in human population. 2,[14][15][16][17][18][19] Certainly, the "response to injury" and the "monoclonal" theories of atherosclerosis are not mutually exclusive and can be unified as described in Figure 2.…”
Section: The Development Of Atherosclerosissupporting
confidence: 69%
“…The human M-CSF receptor (c-fms) monocytic promoter (5.3-kb KpnI-NcoI fragment of c-fms genomic DNA) was kindly provided by C. J. Sherr and was extended at its 3Ј end to within 2 bp upstream of the translation start site. This fragment was digested with either EcoRI or SacI, and the resultant 1.2-kb EcoRI-NcoI and 599-bp SacI-NcoI fragments, after being rendered blunt ended by T4 DNA polymerase, were cloned into a chloramphenicol acetyltransferase (CAT) plasmid (pBS-CAT) that had been digested with EcoRV (12,15,25). Both fragments contain 179 bp of exon 2.…”
Section: Cellsmentioning
confidence: 99%
“…Twenty-five micrograms of total RNA was hybridized with approximately 20,000 cpm of the RNA probe overnight at 42ЊC and then was digested with the mixture of RNase A and RNase T 1 . A specific RNA for human scavenger receptor that was protected from digestion was separated on a 5% acrylamide-8 M urea gel (15).…”
Section: Actgtgacgttc-3ј] Intomentioning
confidence: 99%
See 2 more Smart Citations